Survival and Growth Performance of Catfish Larvae (Anabas testudineus) with Moina sp. Enriched with Viterna: Innovative Application in Aquaculture - Harianto Harianto; Sukendi Sukendi; Yusni Ikhwan Siregar; Benny Heltonika (Jurnal Ilmiah Multidisiplin, 2025)
The Betok fish (Anabas testudineus) is one of the freshwater fish species with potential for aquaculture. Larvae rearing faces challenges, namely low survival rates due to low nutrient content in the feed. Therefore, it is necessary to supplement Moina sp. with viterna. This study aims to determine the optimal dose of viterna in Moina sp. supplementation to improve the survival rate and growth of Betok fish larvae. The method used is an experiment. The experimental design employed is a Complete Randomised Design (CRD) with one factor and three treatments, each repeated three times. The treatments involved enriching Moina sp. with viterna at different doses: D0 = 0 ml/L (control), D20 = 20 ml/L, D40 = 40 ml/L, and D60 = 60 ml/L. The results of the study showed that the enrichment of Moina sp. with different viterna doses affected the survival rate and growth of betok fish larvae. The best treatment was D60, with absolute weight growth of 0.47 g, specific growth rate of 8.01%/day, absolute length growth of 2.64 cm, and survival rate of 93.33%. The water quality parameters obtained included temperature 26–29.1°C, pH 6.3–7.1, and dissolved oxygen (DO) 5.3–6.2 ppm.